THE EFFECT OF RELIGIOSITY ON ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - Ariyanti, Yulekhah (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
Abstract—Religiosity is closely associated with religious activities; not only performing rituals (worship) but also on other activities. Religiosity can predict how a person's work performance is. The purpose of this study is to analyze the level of religiosity of a person through five dimensions; ritual, ideological, intellectual, experience and the dimension of consequences, and to analyse religiosity’s effect on organizational citizenship behavior (OCB). The analytical tool used to test the effect of research variables is multiple linear analysis. The research was conducted using qualitative descriptive analysis with teachers in foundation of Roudlotus Saidiyyah in Semarang as respondents. The study shows no effect of the ritual dimension (X1), the ideological dimension (X2), the intellectual dimension (X3), and the dimension of experience (X4) on OCB, while the dimensions of the consequences (X5) has a considerable influence on OCB. Keywords—Organizational Citizenship Behaviour (OCB); Ritual dimension; Ideological Dimension; Intellectual dimension; the Dimension of Experience; Consequence